Conversational Code-Switching among Bilinguals in Junior High School Reunion Event - Lestari, Firnantia Lara (Humaniora: Journal of Indonesia Culture and Society, 2018)
The goal of this research was to find out the types of code-switching, and the reason of the participantsÂ performs code-switching in the conversation. Research used a qualitative approach. The result shows that threeÂ types of code-switching occurs in the conversation among bilingual in the junior high school reunion, they areÂ intra-sentential mixing, intra-lexical code mixing, involving a change of pronunciation. The functions of codeswitchingÂ usage are as the marker of changing topic, to show their closeness as an old friend, and to show theÂ close relationship among others. The close relationship between the speakers makes the feel free to switch fromÂ one language to another. Furthermore, the switching code also has another function as repetition is used toÂ clarify the utterances of by the speakers. Moreover, the code-switching in the conversation are able to declareÂ the excitement feeling towards a particular topic (the interesting topic) that they are talking about.